Tecnologie e soluzioni per un uso professionale dei PDA di nuova generazione Il caso di iPhone di Apple - Santarsiero, Domenico (GEOmedia, 2010)
The Device so-called Mobile now are "using daily" in the playing camp of geomatic, of the geographic information and the sismographic applications. The article follow a reading of the tecnology evolution and applications of interest for the Geomedia readers.